Neighbourly: A Mobile Application for Uniting Local Engagements in Bandar Springhill - Megat Mahayudin, Puteri Fadlina Aliah; HAFIT, HANAYANTI (Applied Information Technology And Computer Science, 2025)
The Bandar Springhill community, located between Port Dickson and Seremban, traditionally relied on unorganised platforms such as Facebook and WhatsApp groups to access local skills and services. This often resulted in inefficiencies and led residents to seek external resources, overlooking the talents available within their neighbourhood. The Neighbourly platform was developed to address this issue by facilitating structured community interaction and resource sharing. Adopting the Prototype Model, the application was designed and implemented using Android Studio and Flutter for the front end, with Firebase integrated as the real-time backend solution. The prototype features a Login and Registration, User Profile, Skill Listings, Chat, Review and Rating, Volunteering Events, and an Admin Dashboard accessible through unique login credentials. The Neighbourly platform aims to empower Bandar Springhill residents by improving access to local resources, encouraging collaboration, and fostering self-reliance. Ultimately, it seeks to contribute to building a more cohesive, sustainable, and connected neighbourhood.